2022
DOI: 10.3390/nu14061164
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Undernourished Children Under-Five Years Old with Diarrhoea in Mozambique: A Hospital Based Cross-Sectional Study, 2015–2019

Abstract: Diarrhoea is associated with undernutrition and this association is related to increased morbidity and mortality in children under-five. In this analysis we aimed to assess the frequency and associated factors of undernutrition in children under-five with diarrhoea. A hospital-based cross-sectional study was conducted from January 2015 to December 2019 through a surveillance system in five sentinel hospitals in Mozambique. Sociodemographic and clinical information was collected, including anthropometry. A tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 34 publications
(70 reference statements)
1
15
0
Order By: Relevance
“…In Mozambique, in 2015, the prevalence of diarrhea in children under five was 11.0% and 41.7% were stunted, 4.4% were wasted, and 15.6% were underweight [ 13 , 14 , 15 , 16 ]. A Mozambican hospital-based cross-sectional study reported a frequency of 54.1% for undernutrition among children under five with diarrhea [ 17 ]. The child’s nutritional status is an important diarrhea determinant and vice versa, as undernutrition is associated with a greater incidence and duration of diarrhea, and undernutrition is worsened by diarrhea [ 18 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…In Mozambique, in 2015, the prevalence of diarrhea in children under five was 11.0% and 41.7% were stunted, 4.4% were wasted, and 15.6% were underweight [ 13 , 14 , 15 , 16 ]. A Mozambican hospital-based cross-sectional study reported a frequency of 54.1% for undernutrition among children under five with diarrhea [ 17 ]. The child’s nutritional status is an important diarrhea determinant and vice versa, as undernutrition is associated with a greater incidence and duration of diarrhea, and undernutrition is worsened by diarrhea [ 18 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Provincial-level analysis was performed for the whole country. To showcase a detailed district-level analysis, the focus was on the Nampula Province districts, since this province has high rates of undernutrition and diarrhoea in children under 5 years old 5 8 25. Simple linear regression was performed to assess the seasonality component and projection of cases for the year 2020.…”
Section: Methodsmentioning
confidence: 99%
“…Low/middle-income countries (LMICs) face a high burden of disease, especially among children under 5 years old, and infectious diseases and undernutrition remain big concerns in this age group 1. Diarrhoea and undernutrition morbidity and mortality in children under 5 are substantial and, in addition, the two diseases are frequently associated with one another in LMICs 2–5. In 2019, diarrhoea was responsible for 9.9% of deaths in children under 5, and in the same year, 21.9% of children were considered to be stunted worldwide 1 6 7.…”
Section: Introductionmentioning
confidence: 99%
“…Diarrhoea is the passage of three or more watery or loose stools per day 1. It causes the body to lose a substantial amount of salt and water, which can either cause rapid and severe dehydration and death or predispose children to malnutrition and increase their risk of infection 2.…”
Section: Introductionmentioning
confidence: 99%
“…Diarrhoea is the passage of three or more watery or loose stools per day. 1 It causes the body to lose a substantial amount of salt and…”
Section: Introductionmentioning
confidence: 99%